2016
DOI: 10.17795/zjrms-4963
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aspalathin on Levels of Sugar and Lipids in Streptozotocin-Induced Diabetic and Normal Rats

Abstract: Background: Flavonoids have been reported as mammalian alpha-amylase inhibitors, a property which could be useful in the management of postprandial hyperglycemia in diabetes and its related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…Furthermore, both in vitro and in vivo studies have indicated that aspalathin can reduce hyperlipidaemia [91,146]. The effect of aspalathin to diminish cholesterol, triglycerides, and VLDL and LDL cholesterol levels, while increasing high-density lipoprotein cholesterol levels, has been investigated in a few studies.…”
Section: Effect Of Aspalathin On Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Furthermore, both in vitro and in vivo studies have indicated that aspalathin can reduce hyperlipidaemia [91,146]. The effect of aspalathin to diminish cholesterol, triglycerides, and VLDL and LDL cholesterol levels, while increasing high-density lipoprotein cholesterol levels, has been investigated in a few studies.…”
Section: Effect Of Aspalathin On Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Different doses of curcumin and grape seed oil (as solvent of curcumin) were administrated orally for 30 days through a gastric cannula in a single dose (0.5 mL) at 8:30 am. Rats randomly were divided into two major groups: normal rats (N), diabetic rats (D), each was subsequently divided into five subgroups (each group included 6 rats), as defined below: I) normal control group (NO): rats in this group received grape seed oil (O); II) normal experimental groups: rats in these groups received curcumin at 10, 20, 40 and 80 mg/kg (groups were named, NC10, NC20, NC40 and NC80 respectively); III) diabetic control group (DO): rats in this group received grape seed oil (O); IV) diabetic experimental groups: rats in these groups received curcumin at 10, 20, 40 and 80 mg/kg (groups were named, DC10, DC20, DC40 and DC80 respectively) [10,[17][18][19]. Also we considered ethical principles for working with animals.…”
Section: Treatment With Curcuminmentioning
confidence: 99%
“…The first is inhibition digestion of carbohydrates with inhibition of alpha amylase, the enzyme that decomposed of carbohydrates and the second is inhibition of absorption via sodium/glucose co-transporters (SGLT1 and SGLT2), the sugar transporter systems [17,18]. Flavonoid-rich fractions of plants have also been reported to be effective as antihyperglycemic and antihyperlipidemic agents in animal models of diabetes [19]. Plants derived polyphenols such as quercetagetin, fisetin and quercetin, which belong to the flavonoid family have been shown to be effective inhibitors of mammalian alphaamylase with IC50s in the order of micromolar [20].…”
Section: Introductionmentioning
confidence: 99%
“…Interest among the food and nutraceutical industries in the production of extracts from rooibos ( Aspalathus linearis ) has developed during the past 20 years, fuelled to a large extent by its antioxidant activity. Recent studies have focussed on aspalathin, a C ‐glucosyl dihydrochalcone unique to rooibos, providing in vitro and in vivo evidence of its antidiabetic and anti‐inflammatory properties . Subchronic feeding of type 2 diabetic model (KK‐A y ) mice with a cold‐water based green rooibos extract containing 66 g kg −1 aspalathin suppressed the increase in their fasting blood glucose levels .…”
Section: Introductionmentioning
confidence: 95%